PENGARUH VARIASI OKSIGEN TERHADAP LAJU KEMATANGAN KOMPOS - IDAA Warmadewanthi (Purifikasi, 2003)
Rotatable reactors were used in this experiment. Oxygen was continously supplied into the reactors until the compost was mature. Using a motor, the rectors were rotated daily at a speed of 1.5 rpm for 5 revolutions. Domestic waste sludge was added to the reactor to have an initial C/N ratio of 30. The sludge was mixed with the compost before being inserted to the reactors. The results showed that oxygen of 9.07-114.4 l/kg.day was required in order a mature compost within 7 days. This was proved by having a C/N ratio of < 20 and stable temperature. The compost quality was adequate as shown by the pH of 6-8.5 with N concentration of 2.2-2.5%, P of 0.21% and K of 0.34%.